A STUDY ON BIOCHEMICAL PROPERTIES AND ANTIOXIDANT ACTIVITY OF HONEY FROM DERA BUGTI DISTRICT OF BALOCHISTAN - S. Ambreen; Z. Mehmood; K. Mehmood; A. Sajjad; A. Mushtaq; S. Rizwan; U. Jabeen; F. Bashir; F. Behlil (Journal of Animal and Plant Sciences, 2022)
20 honey samples from district, Balochistan (Pakistan) were studied for their physiochemical, biochemical and antioxidant potential. During the study, pH, ash content, moisture, total fat, sugar content, reducing and non-reducing sugars, vitamin C, Vitamin A, flavonoids, polyphenols and % DPPH scavenging activity were monitored. The pH of the samples was between4.0 - 5.0, having mean±SD values of 4.5 ± 0.1. The moisture and ash content had an average value of 17.4 ± 0.7 g/100g and 0.142 ± 0.0 g/100g respectively. The fat content had range of values from minimum to maximum 0.12 - 0.49 g/100g with mean±SD of 0.297 ± 0.11. Total sugar content varied between 66.2 - 71.8 g/100g with mean and S.D 68.88 ± 1.7. The sucrose content ranged between 0.60 - 4.28 g/100g with mean±SD 1.93 ± 0.8 while average value of fructose and glucose values were 36.84g/100g ± 0.9 and 30.41g/100g ± 3.00 respectively. All the tested samples showed very low content of Vitamin A while Vitamin C and flavonoids showed the average values of 112.45 ± 9.8 mg/kg and 43.0 ± 2.0 mg CE/kg respectively and polyphenols showed the average value of 748.76 ± 31.6 mg GAE/kg with 6057.5 - 887.2 mg GAE/kg min to max values. The % DPPH scavenging at 40mg/ml showed the values 61.8 - 75.7 min to max with the average of 70.3 ± 0.9. All the tested samples lie within the limits of international standard but Sample P4 showed the best results among all the 20 honey samples.
Keywords: Honey; composition; biochemical; physiochemical; Antioxidant; flavonoids; total Sugars